2018
DOI: 10.1149/2.0331815jes
|View full text |Cite
|
Sign up to set email alerts
|

Facile Preparation and High Activity of TiO2Nanotube Arrays toward Oxygen Reduction in Alkaline Media

Abstract: Four TiO 2 electrodes have been investigated for the oxygen reduction reaction (ORR) in 2 M NaOH. Anodic oxidation of Ti-foil was used as the final or the first step in the preparation of four electrodes based on TiO 2 : amorphous (Ti/AM-TiO 2 ), two anatase forms (Ti/A400-TiO 2 and Ti/A550-TiO 2 ), and, finally, lithium-anatase form (Ti/A-Li 0.25 TiO 2 ), all of them obtained as TiO 2 nanotube arrays. The electrodes' structure was examined by Raman spectroscopy. Cyclic voltammetry and chronoamperometry were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…In the Raman spectrum of the TiO 2 NTs five Raman active modes are observed at 148 cm −1 (E g ), 204 cm −1 (E g ), 394 cm −1 (B 1g ), 515 cm −1 (A 1g , B 1g ) and 636 cm −1 (E g ), which correspond to the anatase phase. 40,45,46 TiO 2 NTs morphology was investigated by SEM, Figs. 2a-2b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Raman spectrum of the TiO 2 NTs five Raman active modes are observed at 148 cm −1 (E g ), 204 cm −1 (E g ), 394 cm −1 (B 1g ), 515 cm −1 (A 1g , B 1g ) and 636 cm −1 (E g ), which correspond to the anatase phase. 40,45,46 TiO 2 NTs morphology was investigated by SEM, Figs. 2a-2b.…”
Section: Resultsmentioning
confidence: 99%
“…In the investigation our research group conducted with Ti/TiO 2 NTAs electrodes in 2 M NaOH, it was shown that lithiated anatase phase Li 0.25 TiO 2 was a better electrocatalyst for oxygen reduction reaction comparing to both anatase and amorphous TiO 2 NTs. 40 TiO 2 NTs with their tunable diameter and length can offer large exposed surface area and porosity which together with short diffusion length of Li-ion can significantly improve electrochemical performance for an anode in LIBs. The review papers of N.A.…”
mentioning
confidence: 99%